Statistical Evaluation of the Cost-Effectiveness of the Choice of the Treatment Type for Breast Cancer - Kovtun, N. V.; Motuziuk, I. M.; Ganzha, R. O. (Statistics of Ukraine, 2021)
In order to calculate the overall economic effect of the one-stage reconstruction surgery, a methodological approach was developed. The approach is based on the two components: for the “fast-track surgery” (FTS) – the economic effect of the decrease of in-hospital stay given one-step reconstructive surgery is performed compared to modified radical type of surgery, and economic effect of savings on the cost of treatment for patients with breast cancer using one-step reconstructive surgery compared with modified radical mastectomy at different stages of treatment. Although, at the first glance, the modified radical mastectomy appeared to be more cost-effective type of treatment as compared to the one-time reconstruction, after taking into account all the factors and components making up the cost of treatment, it was proved that under the long run patients will need at least two reconstruction surgeries, and the cost of care can increase by almost 93%. According to the results of the calculations, the amount of overall savings was determined, as well as the magnitude of the economic effect for particular types of surgery. The economic effect was also extended to the number of registered patients, taking into account the trend of breast cancer incidence in Ukraine for 5 years. The results of calculations for the proposed two-component approach showed that the total amount of economic effect during the one-time reconstructions with an implant can be estimated at an average of 76740 UAH per patient. In turn, the economic efficiency was estimated at 42.2%. Extension of these data on the number of registered patients and additionally considering the continuing trend of breast cancer incidence in Ukraine for 5 years showed that the total amount of savings on implants for government and households will exceed 1 billion 100 million UAH, and for 5 years this amount will average in more than UAH 6.7 billion. On top of this, one-time reconstructions include an additional social effect, which is expressed not only in the decrease of the length of stay in the hospital, but also in improving the quality of life, which, in turn, reduces the risk of complications and recurrences in the future.